Male Partners’ Involvement during Antenatal Visit and Its Associated Factors among Pregnant Women Attending Hawassa City Public Health Facilities, Hawassa, Sidama Region, Ethiopia - Tefera, Kebede; Birhanu, Selamawit (Pharma Multidisciplinary Research Journal, 2024)
Background: - Male partner’s involvement in ANC is important to minimize delays in decisions to seek antenatal care. Despite improved accessibility, delays in pregnant women seeking their first ANC remain a challenge. This study is aimed to assess male partner involvement during utilization of antenatal care and its associated factors among pregnant women attending Hawassa city public health facilities. Methods – An institution based cross-sectional study was employed in Hawassa city public health facilities from July 1-30, 2022. Systematic random sampling techniques used for recruitment 406 participants. Data were collected using structured pretested questionnaire by interview administered technique. Data collected via interviews and analyzed in SPSS, employing logistic regression to assess factors influencing male involvement. Results, with a significance level of p < 0.05, were presented through tables, figures, and text, including crude and adjusted odds ratios. Result- In this study 406 respondents participated in the study giving response rate of 96%. The mean age of participants was 24.35(+Sd 4.5) yrs. Overall prevalence of male partner involvement ANC visit was 70.4% with 95 % confidence interval (65.99, 74.90). Planed pregnancy AOR 2.9 [95% CI (1.4, 6.1)] times and health worker cooperation AOR 3.4 [95% CI (1.8, 6.3)] times predict the involvement of male partner during ANC service utilization. Conclusion - Male partner involvement in antenatal care visit is high in Hawassa city public health facilities. Factors like planned pregnancy and health worker cooperation contribute to the outcome. Stakeholders should actively educate men about the importance of their involvement in antenatal care to enhance participation.